N-[3-(Prop-1-yn-1-yl)phenyl]benzenesulfonamide - Pineda Cedeño, Leslie William (2019)
In the title sulfanilamide derivative, C15H13NO2S, which shows significant activity against Staphylococcus aureus and Escherichia coli, the dihedral angle between the planes of the aromatic rings is 62.15 (19)° and the four-coordinate S atom adopts an almost ideal tetrahedral geometry. In the crystal, N—H. . .O and C—H. . .O hydrogen bonds link the molecules into a three-dimensional network.